Caracterização química de drogas sintéticas apreendidas em Minas Gerais - Nathalia Paiva da Silva (2018)
In this work the characterization of synthetic drugs seized in the state of Minas Gerais was carried out with the objective of tracing a chemical profile of the illicit drugs marketed in the form of tablets. For that, 141 tablets seized by the Civil Police of Minas Gerais in different colors and formats were analyzed. They were separated into classes called amphetamine-type stimulants (ATS), synthetic cathinones andother new psychoactive substances (NPS). Analyzes were performed by PS-MS and GC-MS for the identification of organic constituents and analysis by ICP-MS and TXRF for quantification of inorganic constituents. For PS-MS analysis, about 2 mg of each tablet were weighed and solubilized in 200 L of methanol and the analyzes were performed in the positive mode. From the data obtained by the PS-MS it waspossible to identify/classify the seized tablets, of which 58 were3,4-methylenedioxymethamphetamine (MDMA) and 55 synthetic catinones, including 15 tablets of n-ethylpentylone and 9 of dibutylone. For analysis by GC-MS about 2 mg of tablet were solubilized in 1 mL of methanol and centrifuged. A SPME fiber was immersed in the solution containing the analytes and then injected into the portable equipment. This technique enabled the identification of compounds used inthe drug synthesis process, as well as intermediate and adulterating compounds, such as 3,4-methylenedioxyphenyl-2-propanone which was found in 84% of MDMA tablets. Analyzes by TXRF and ICP-MS were complementary and were able to give important information regarding the catalysts used in the synthesis, used diluents and impurities. ATS is most commonly found in the form of hydrochloride and syntheticcathinones in the form of hydrobromide. Platinum was present in100% of ATS tablets and the concentration of aluminum is much higher in synthetic cathinones than in ATS. The results obtained in this dissertation were sufficient for a detailed characterization and to demonstrate the applicability of these techniques as an alternative for NPS analysis.